1997
DOI: 10.1159/000262394
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of the Effect of Prenatal Fluoride Supplements in Preventing Dental Caries

Abstract: This randomized, double-blind study tested the caries-preventive efficacy of prenatal fluoride supplementation in 798 children followed until age 5. Initially, 1,400 women in the first trimester of pregnancy residing in communities served by fluoride-deficient drinking water were randomly assigned to one of two groups. During the last 6 months of pregnancy the treatment group received 1 mg fluoride daily in the form of a tablet and the control group received a placebo. Both treatment and control subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 5 publications
0
44
0
3
Order By: Relevance
“…Primary teeth were protected against caries even though prenatal incorporation of fluoride into unerupted teeth was insignificant. Additionally, a randomized, doubleblind, longitudinal study testing the caries-preventing efficacy of prenatal fluoride supplementation in children followed until age 5 failed to support the hypothesis that prenatal fluoride has a strong caries-preventive effect [Leverett et al, 1997]. Hellwig and Klimek [1985] found that children 12.5-16 years old who had been exposed all their life to naturally fluoridated water exhibited significantly fewer carious lesions compared to a control group.…”
mentioning
confidence: 99%
“…Primary teeth were protected against caries even though prenatal incorporation of fluoride into unerupted teeth was insignificant. Additionally, a randomized, doubleblind, longitudinal study testing the caries-preventing efficacy of prenatal fluoride supplementation in children followed until age 5 failed to support the hypothesis that prenatal fluoride has a strong caries-preventive effect [Leverett et al, 1997]. Hellwig and Klimek [1985] found that children 12.5-16 years old who had been exposed all their life to naturally fluoridated water exhibited significantly fewer carious lesions compared to a control group.…”
mentioning
confidence: 99%
“…30 Suplementos de flúor, como medicamentos, são de prescrição individual, sem efetividade como medida de Saúde Pública.…”
Section: Resultsunclassified
“…More recently, a clinical trial [Leverett et al, 1997] on prenatal fl uoride supplements did not demonstrate a correlation between prenatal fl uoride exposure and caries experience of the sample studied. In the present study fl uoride concentrations were analyzed in enamel and den-…”
mentioning
confidence: 90%
“…Primary teeth were collected from a randomized, double-blind study of prenatal fl uoride supplementation in 798 children followed until age 5 [Leverett et al, 1997]. During the duration of the study parents were encouraged to mail in their children's primary teeth as they exfoliated, in envelopes previously provided by the study committee.…”
Section: Teethmentioning
confidence: 99%
See 1 more Smart Citation